A Multi-Mode Bioactive Agent Isolated From Ficus microcarpa L. Fill. With Therapeutic Potential for Type 2 Diabetes Mellitus - Akhtar, Nosheen; Jafri, Laila; Green, Brian D; Kalsoom, Saima; Mirza, Bushra (Frontiers in Pharmacology, 2018)
Type 2 diabetes is a metabolic disorder, characterised by hyperglycemia and glucose intolerance. Natural products and its derived active compounds may be achievable alternatives for the treatment of type 2 diabetes. In present study we investigated the antidiabetic potential of Ficus microcarpa and isolated bioactive compounds i.e. Plectranthoic acid A (PA-A) and 3,4,5,7-Flavantetrol (FL). Anti-hyperglycemic potential was evaluated via α-glucosidase, α-amylase and dipeptidyl peptidase 4 (DPP-4) assays. 5′AMP-activated kinase (AMPK) activation potential was assessed by using primary hepatocytes. Distribution of PA-A in different parts of Ficus microcarpa was evaluated by using rapid high-performance liquid chromatography (HPLC). Ethyl acetate fraction (FME) exhibited significant inhibition of α-glucosidase, α-amylase and DPP-4, therefore, was selected for isolation of bioactive compounds. Among isolated compounds PA-A was more potent and possessed pleotropic inhibitory activity with IC50 values of 39.5, 55.5 and 51.4 µM against α-glucosidase, α-amylase and DPP-4, respectively. Our results showed that PA-A is also a potent activator of AMPK which is a central hub of metabolic regulation. Molecular docking studies confirmed the activity of PA-A against α-glucosidase, α-amylase and DPP-4. Rapid HPLC method revealed that maximum concentration of PA-A is present in the stem (2.25 µg/mg dry weight) of Ficus microcarpa. Both in vitro and in silico studies proposed that Ficus microcarpa and its isolated compound PA-A could be an important natural source for alleviating the symptoms of type 2 diabetes mellitus and we suggest that PA-A should be explored further for its ultimate use for the treatment of type 2 diabetes.